Pengaruh Intensitas Modal, Ukuran Perusahaan Dan Sales Growth Terhadap Tax Avoidance : (Studi Empiris Pada Perusahaan Industrials Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2017-2021 ) - maulidiya Zahra Almasah; Fina Fitriyana (Shofanah Media Berkah, 2023)
The purpose of this research is to determine the effect of capital intensity, company size, and sales growth on tax avoidance. The independent variables in this study are capital intensity, company size, and sales growth, while the dependent variable is tax avoidance. The object of this research is to industrial companies listed on the Indonesia Stock Exchange from 2017-2021. This type of research is quantitative with the data collection method used as the secondary method obtained from the website www.idx.co.id. The population in this study was 55 companies. The sampling method was 13 companies with research for 5 years so 65 observation data were obtained. Data processing using Ms. Office Excel and the EViews 10 application program. Based on the results of simultaneous hypothesis testing (F test), capital intensity variables, company size and sales growth affect tax avoidance. The results of partial hypothesis testing (T-test) show that the capital intensity variable and company size have no effect on tax avoidance, while the sales growth variable has a negative effect on tax avoidance.